(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines the role of the green economy in achieving sustainable development goals in developing countries by analyzing its theoretical framework and key strategies. The study adopts a descriptive-analytical approach by reviewing relevant literature and previous studies. Findings indicate that the green economy serves as a strategic pathway to sustainable development by promoting economic growth, improving efficient resource utilization, protecting the environment, and providing decent job opportunities while ensuring social equity. The study concludes that successful implementation of green economy policies in developing countries requires flexible legislative frameworks, increased renewable energy investments, support for environmental innovation, and enhanced international cooperation for technology transfer.